Industrial experience with Fukushima Daiichi accident wastewater treatment: Part II. Issue 9 (September 2021) - Pabby, A.K.; Swain, B.; Mittal, V.K.; Valsala, T.P.; Sathe, D.B.; Bhatt, R.B.
Abstract : Based on existing information, this article, which is published in two instalments, focuses on the challenges of radionuclide removal and analysis of the performance of processes associated with the treatment of a large-scale volume of wastewater at the site of the Fukushima Daiichi nuclear disaster, which occurred ten years ago.